Single Lipid Bilayers Constructed on Polymer Cushion Studied by Sum Frequency Generation Vibrational Spectroscopy - Wang, Ting (2011)
Planar solid supported single lipid bilayers on mica, glass, or other inorganic surfaces have been widely used as models for cell membranes. To more closely mimic the cell membrane environment, soft hydrophilic polymer cushions were introduced between the hard inorganic substrate and the lipid bilayer to completely avoid the possible substrate-lipid interactions. In this article, sum frequency generation (SFG) vibrational spectroscopy was used to examine and compare single lipid bilayers assembled on the CaF(2) prism surface and on poly (L-lactic acid) (PLLA) cushion. By using asymmetric lipid bilayers composed of a hydrogenated 1,2-dipalmitoyl-sn-glycerol-3-phosphoglycerol (DPPG) leaflet and a deuterated 1,2-dipalmitoyl-(d62)-sn-glycerol-3-phosphoglycerol (d-DPPG) leaflet, it was shown that the DPPG lipid bilayers deposited on the CaF(2) and PLLA surfaces have similar structures. SFG has also been applied to investigate molecular interactions between an antimicrobial peptide Cecropin P(1) (CP1) and the lipid bilayers on the above two different surfaces. Similar results were again obtained. This research demonstrated that the hydrophilic PLLA cushion can serve as an excellent substrate to support single lipid bilayers. We believe that it can be an important cell membrane model for future studies on transmembrane proteins, for which the possible inorganic substrate-bilayer interactions may affect the protein structure or function.